Effect of hypoxia-inducible factor-1α induction by CoCl 2 on breast cancer cells survival: influence of cytochrome-c and survivin (Faculty of Medicine Universitas Indonesia, 2014)
Background: Tumor tissue usually became hypoxic due to disruption of oxygen supply. Adaptation response to hypoxia is mediated by transcription factor, hypoxia- inducible factor-1α (HIF-1α). HIF-1α signaling is known to increase the expression of pro-apoptotic protein cytochrome-c, and anti- apoptotic survivin. In this study we wanted to analyze the role of HIF-1α on breast cancer cells survival through pro-apoptosis cytohrome-c and anti-apoptosis survivin regulation. Methods: Breast cancer cell lines T47D were induced by CoCl 2 then harvested to analyze the expression of HIF-1α, protein cytochrome-c, mRNA survivin and cell viabilities Results: HIF-1α induction by CoCl2 causes the increase of protein and mRNA of HIF-1α, cytochrome-c protein, and survivin mRNA, but does not cause the changes in cell viability. Conclusion: HIF-1α induction have no effects on breast cancer cell line T47D viabilities due to the balance regulation between pro-apoptosis expression cytochrome-c and anti-apoptosis survivin.